2020
DOI: 10.1016/j.cophys.2020.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism of cooperative regulation of calcium-sensing receptor-mediated cellular signaling

Abstract: Calcaium sensing receptors (CaSRs) play a central role in regulating extracellular calcium (Ca 2+ ) homeostasis and many (patho)physiological processes. This regulation is primarily orchestrated in response to extracellular stimuli via the extracellular domain (ECD). This paper first reviews the modeled structure of the CaSR ECD and the prediction and investigation of the Ca 2+ and amino acid binding sites. Several recently solved X-ray structures are then compared to support a proposed CaSR activation model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Importantly,TNCA (500 mM) was able to reverse the effect of E297K mutation on both sensitivity (3.10 AE 0.13 mM, N = 20, p < 0.0001) and cooperativity (Hill coefficient:3 .08 AE 0.40 with TNCA vs.2 .12 AE 0.18 without TNCA), supporting co-activation working model (Figures 6C-E and Figures S19J,K). [35][36] In addition, R-CatchER was able to detect ER Ca 2+ oscillations triggered by 1.0 mM extracellular Ca 2+ and 10 mMo ft he CaSR allosteric activator Cinacalcet in ahuman medullary Ccell carcinoma cell line TT,with wider and lower frequent peaks (Figure 6F).…”
Section: Methodsmentioning
confidence: 96%
“…Importantly,TNCA (500 mM) was able to reverse the effect of E297K mutation on both sensitivity (3.10 AE 0.13 mM, N = 20, p < 0.0001) and cooperativity (Hill coefficient:3 .08 AE 0.40 with TNCA vs.2 .12 AE 0.18 without TNCA), supporting co-activation working model (Figures 6C-E and Figures S19J,K). [35][36] In addition, R-CatchER was able to detect ER Ca 2+ oscillations triggered by 1.0 mM extracellular Ca 2+ and 10 mMo ft he CaSR allosteric activator Cinacalcet in ahuman medullary Ccell carcinoma cell line TT,with wider and lower frequent peaks (Figure 6F).…”
Section: Methodsmentioning
confidence: 96%
“…The first one is pyrrolizidine alkaloids, found in both Palaui and Laiban honey. The compound lycoperodine-1 (Table S1) is considered an agonist of Ca 2+ sensing receptors (CaSR) implicated in many diseases [42]. Equally important is the reversible transformation of pyrrolizidine alkaloids to the more hydrophobic N-oxide form [43].…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed an identical result. The binding sites of extracellular Ca 2+ in hCaSR are five extracellular domain regions 31 . In cCaSR, only one amino acid (Ser-388) in Site 4 was mutated to Thr among these important sites.…”
Section: Discussionmentioning
confidence: 99%